Biophysical characterization of the impact of electromagnetic and ultrasonic waves on biological objects - Kalinichenko, S; Antusheva, T; Korotkykh, O; Babych, E; Kivva, F; Kovaneko, O; Ryzhkova, T; Balak, A (Annals of Mechnikov’s Institute, 2020)
In recent years the physical mechanisms of action of electromagnetic fields on biological objects are actively studied. Extensive research about the effect of weak electromagnetic waves on biological objects were launched in the second half of the 60-ies of XX century. It has been suggested that the millimeter waves to biological objects are natural and are used by cells to control basic physiological functions. This review is summarizes the data of foreign and domestic literature related to influence of electromagnetic and ultrasonic waves on biological objects. The concepts of sound waves and electromagnetic field are sanctified. Several hypotheses and points of view of mechanisms of action of microwave radiation on biological objects were discussed in details. One of the hypotheses suggests that the acoustic vibrations of extremely power range can stimulate the cell plasma membrane. Other hypothesis of the mechanism of influence weak signals on biological systems are associated with the discovery of the phenomenon of stochastic resonance. It is assumed that the initiation of acoustic-electrical waves in the lipid-protein membrane of the cell activates the transport of water, ions and various substances through it. The data about the effect of electromagnetic millimeter waves on photosynthetic organisms have been summarized by several scientists. They established that exposure in the microwave range is realized on the membrane level and is connected with the change of oscillation spectrum. Peculiarities of influence of ultrasonic waves on microorganisms and cell membranes have been analysed. Scientists have discovered that detonation of dichloride nitrogen takes place under the influence of ultrasonic waves. Dichloride nitrogen causes breakdown of protein particles. Cavitation effect is one of bactericide action of ultrasonic waves. The mechanism of action of ultrasonic waves in the literature is explained by two theories: cavitation-mechanical, cavitation-electrochemical. According to the first theory of ultrasonic waves propagating in a dense environment, causing it to alternating compression and decompression. Cavitation-electrochemical theory explains the ionization liquid vapor and the presence in it gases in the formation of cavitation bubble. Аn electric discharge occurs at break bubbles. The electrical discharge accompanied by a sharp rise in temperature and in the formation of cavitation bubble electric high voltage charge. Then the vapor of the liquid and high molecular weight compounds in the cavitation chamber are split into hydrogen and hydroxyl groups with formation of active oxygen, hydrogen peroxide, nitrous acid and nitric acid, resulting in inactivation of enzymes and proteins coagulate. All this causes the death of microbial cells. As well ultrasonic vibrations can be used to initiate chemical reactions, the commission of a number of new methods of synthesis and accelerate the slow reactions in organic systems. One of the actions of the ultrasonic waves on microorganisms is a change of concentration various substances in the cytoplasm due to a change of the equilibrium concentration of substances inside and outside the cell. It was found that the effects can be different. On the one hand, researchers observed an increase in the agglutination and the loss or total loss of virulent bacteria. On the other hand there was opposite effect - increasing the number of viable cells. Application of ultrasound in medical microbiology is theoretically proved in this article. Ultrasonic techniques in microbiology used not only as an effect on biological objects and the ability to change the physico-chemical characteristics of substrates for culturing microorganisms. Application of such techniques is important for controlling the composition of artificial culture medium, in particular the concentration and the activation of molecular oxygen by ultrasonic degassing culture medium.